Canonical and Non-canonical TGFβ Signaling Activate Autophagy in an ULK1-Dependent Manner - Trelford, Charles B.; Di Guglielmo, Gianni M. (Frontiers in Cell and Developmental Biology, 2021)
The mechanism(s) in which TGFβ modulates autophagy in cancer remain unclear. Here, we characterized the TGFβ signalling pathways that induce autophagy in non-small cell lung cancer cells, using cells lines stably expressing GFP-LC3-RFP-LC3DG constructs that measure autophagic flux. We demonstrated that TGFβ1 increases Unc 51-like kinase 1 (ULK1) protein levels, AMPK-dependent ULK1 phosphorylation at serine (S) 555 and decreases mechanistic target of rapamycin (mTOR) activity on ULK1. Further analysis revealed that the TGFβ activated kinase 1/tumour necrosis factor receptor-associated factor 6/P38 mitogen activated protein kinase (TAK1-TRAF6-P38 MAPK) pathway and Smad4 were important for TGFβ1-induced autophagy. The TAK1-TRAF6-P38 MAPK pathway was essential for downregulating mTOR S2448 phosphorylation, AMPK-dependent ULK1 S555 phosphorylation and autophagosome formation. Furthermore, although siRNA-mediated Smad4 silencing did not alter mTOR-dependent ULK1 S757 phosphorylation, it did reduce AMPK-dependent ULK1 S555 phosphorylation and autophagosome formation. Our results suggest that the Smad4 and TAK1-TRAF6-P38 MAPK signalling pathways are essential for TGFβ-induced autophagy and provide specific targets for the inhibition of TGFβ in tumor cells that utilize autophagy in their EMT program.